Impact of Reverse Globalization on the Competition in EU Digital Markets - Radukic, Snezana; Popović, Andrija (Industrija, 2021)
This paper aims to analyze the relationship between reverse globalization, the digital markets, and competition policy within the EU. Based on the review of contemporary literature, this paper provides an insight into the EU adaptation to the changes caused by the Covid-19 pandemic. Reverse globalization is identified through the trends in the international trade and FDI flows, while the digital markets' development is evaluated through the Number of individuals using the Internet to order goods and services and E-Commerce sales. While this paper uses secondary data sources, it uniquely connects the identified reverse globalization and digital markets expansion with necessary changes in the competition policy pre and during the Covid-19 pandemic. Additionally, this paper provides policymakers and business owners with relevant information and possible avenues to improve the competition policy and business strategy.
Keywords: Reverse Globalisation, Digital Markets, Economic Development, Covid-19, Competition Policy